(untitled) (Journal of Asian Development Studies, 2023)
For a long time, it was considered that a nation can only benefit from economic success. Due to this, all the financial decisions made were in favour of increasing production levels, neglecting that there could be a cost to all this activity. Financial inclusion has the potential to impact the environment in ways. It can lead to increased and eased business activities, which may result in higher production levels and CO2 emissions. Increased levels of CO2 have a greater capacity to hamper growth through economic changes in the form of global warming, financial costs, resource scarcity, and other regulatory and market changes, which are again challenging and risky to resolve. This paper examines the relationship between inclusive finance and environmental quality in China using the ARDL econometric technique. The analysis is based on a time series dataset spanning 55 years, from 1965 to 2020. Upon conducting the Augmented Dickey-Fuller (ADF) test, it is evident that all the variables exhibit a unit root at a significance level of 1%. The research findings indicate that a marginal rise of 1% in financial inclusion, industrialization, population, economic growth, and energy consumption corresponds to a concomitant increase of 1.0%, 2.60%, 40%, 1.45%, and 1.0% in carbon dioxide (CO2) emissions. The findings of this study indicate that the development of accessible financial systems should be prioritized as a strategic approach to address the challenges posed by climate change. It is crucial to minimize the adverse impacts of financial inclusion on environmental quality and foster equitable and sustainable economic growth.